Different radiographic imaging modalities with a proton computed tomography demonstrator. (1st January 2022) - Kaser, S.; Bergauer, T.; Burker, A.; Frötscher, I.; Hirtl, A.; Irmler, C.; Pitters, F.; Ulrich-Pur, F.
Abstract: Proton computed tomography aims at improving proton-beam therapy, which is an established method to treat deep-seated tumours in cancer therapy. In treatment planning, the stopping power (SP) within a patient, describing the energy loss of a proton in a tissue, has to be known with high accuracy. However, conventional computed tomography (CT) returns Hounsfield units (HU), which have to be converted to SP values to perform the required treatment planning, thus introducing range uncertainties in the calculated dose distribution. Using protons not only for therapy but also for the preceding planning CT enables the direct measurement of the SP. Hence, this imaging modality eliminates the need for further conversion and therefore offers the possibility to improve treatment planning in proton therapy. In order to examine the principles of such a proton CT (pCT) setup, a demonstrator system, consisting of four double-sided silicon strip detectors and a range telescope, was built. The performance of the pCT demonstrator was tested with measurements at the MedAustron facility in Wiener Neustadt, Austria. In this paper, 2D imaging modalities going beyond the idea of a standard proton radiography, will be discussed. Namely, fluence loss imaging and scattering radiography results obtained with the demonstrator will be shown. The advantage of these modalities is that they do not rely on an additional energy measurement and can therefore be conducted only with the tracker of the demonstrator.